Socioeconomic and environmental effects from sugarcane expansion in to the Pontal do Paranapanema region - Egeskog, Andrea; Gustafsson, Stina (My University, 2007)
Pontal do Paranapanema is the only region in São Paulo state where a large scale sugarcane expansion can take place. Such expansion is expected and will likely affect the rural family farmers in the region. Without regulations, the expansion might negatively affect the income of family farmers who start to grow sugarcane. Some family farmers already grow sugarcane and it has been shown that their average income from sugarcane is sometimes less than 3 times the average income from sugarcane in the rest of the state. The same is expected to be the case for all family farmers who start to grow sugarcane if no regulations are added. The family farmers have such small properties that it is not profitable for them to buy all necessary equipment for growing sugarcane. They rent some services from the sugarcane industry leading to lower net incomes. The sugarcane expansion can lead to increased socioeconomic benefits for the family farmers if the expansion is done in combination with changed cattle farming. Family farmers can have a combined production system where they grow sugarcane on parts of their property and in exchange for the delivered sugarcane to the sugarcane industry they could receive nutritious cattle feed made from sugarcane residues. If the cattle stock is changed and feed with the cattle feed this can lead to large increases in milk production and hence large income gains. To evaluate the socioeconomic and climate impacts of expanding ethanol sugarcane production in conjunction with this combined production system, two models were created: one for calculating income growth of family farmers when a combined sugarcane and milk production system is introduced and one for calculating energy and emissions from a sugarcane expansion when coupled with the combined production system. The model analyses indicate that income could 10-fold for family farmers if a combined sugarcane and milk production system is introduced. At the same time, the global emissions of greenhouse gases could be significantly reduced if the ethanol from such production replaced gasoline used for transportation in the EU. If a sugarcane industry wants to run in Pontal regulations could state that they then have to produce cattle feed of some of the sugarcane residues in order to promote the combined production system.
Keywords: Energi; Hållbar utveckling; Miljöteknik; Teknik och social förändring; Energy; Sustainable Development; Environmental engineering; Technology and social change